17. EVALUATION OF THE EFFECTIVENESS OF TREATING CHRONIC LUMBAR RADICULOPATHY WITH STEROID EPIDURAL BLOCKAGE (Vietnam Journal of Community Medicine, 2024)
Objective: To evaluate the treatment outcomes of chronic lumbar radiculopathy using steroid epidural nerve block.Subjects and Methods: A non-controlled interventional study involving patients with chronic radiculopathy treated with steroid epidural nerve block at Thong Nhat Hospital, Ho Chi Minh City, from June 2023 to January 2024.Results: The VAS scores after intervention at 1 week, 1 month, and 3 months were 4.3 ± 0.78, 3.2 ± 0.9, and 3.2 ± 0.9, respectively, showing a significant reduction compared to the pre-intervention VAS score of 7.3 ± 0.3. One case of transient exacerbation of pain was noted.Conclusion: The application of steroid epidural nerve block is a preliminary method that demonstrates effectiveness and safety.
Keywords: chronic lumbar radiculopathy; steroid; epidural blockage